Esketamine in Treatment-Resistant Depression and Suicidal Ideation: A Systematic Review - Dudziak, Natalia; Drozd, Zuzanna; Niemiec, Bartosz; Piosik, Szymon; Olesiński, Bruno; Piasecki, Łukasz; Guzowicz, Zuzanna; Kamińska, Monika; Gągałka, Patrycja (Journal of Education, Health and Sport, 2025)
Background. Major depressive disorder affects 20% of the global population, with treatment-resistant depression in 10-30% of cases. Patients with acute suicidal ideation need immediate intervention, yet conventional antidepressants require weeks to work. Esketamine offers rapid symptom reduction through NMDA receptor antagonism. Aim. To systematically review current evidence on efficacy and safety of esketamine nasal spray in treating depression with active suicidal ideation and treatment-resistant depression, focusing on rapidity of response and clinical outcomes. Material and methods. PubMed search using terms "esketamine, depression, suicide" and related. After screening, 11 studies from 2020 onwards were analyzed. Results. ASPIRE II showed esketamine 84mg superior to placebo at 24 hours: MADRS reduction -15.7 vs -12.4 points (p=0.006), with effects at 4 hours. In 456 patients, response rates were 34.5% vs 25.3%, remission 20.4% vs 9.8% at 24 hours. Versus quetiapine, esketamine achieved 27.1% vs 17.6% remission at week 8 (p=0.003). Long-term data (1,148 patients, 31.5 months) showed suicide attempts 0.361 and deaths 0.036 per 100 patient-years. Common side effects: dizziness (38-47%), nausea (27-33%), transient dissociation; 4-11% discontinued treatment. Conclusions. Esketamine demonstrates rapid efficacy in reducing depressive symptoms and suicidal ideation, with effects within hours and sustained benefits. It shows superior results versus placebo and comparators with acceptable safety, making it valuable for acute suicidal ideation requiring rapid intervention.